A Takmilah Reading of Spiritual Imagery in the Poems of Abizai Abi: (Citra Kerohanian dalam Puisi Abizai Abi daripada Bacaan Takmilah) (Malay Literature, 2018)
This article focuses on a number of poems by Zainal Abidin Bin Haji Suhaili, better known as Abizai Abi, in his anthology of poems entitled Sinar Benar [True Ray of Light]. Abizai has been prolific in producing beautiful and meaningful poems of high quality. However, not many in-depth studies of his works have been conducted. This study attempts to examine several poems selected from Sinar Benar by employing the Takmilah Theory. Being an important writer in Malaysia, especially in the state of Sarawak, Abizai stands out through his application of spiritual imagery, in line with his framework of thought consistently anchored in the "relationship between human beings and Allah". This framework of thought encompasses issues of piety and obedience to Allah (SWT), which is entirely in line with the Takmilah Theory. This study finds that the beauty of Abizai Abi's poetry lies in its refined, meaningful and effective language. The poems studied also reveal that a good relationship between human beings and nature is the basis of a good relationship with the Great Creator. Abizai Abi's thinking is conveyed through the diction of his symbolism, which foregrounds "piety" and "utter humility". He attempts to demystify nature and examine it spiritually, and relate it to the Greatness and Might of Allah (SWT) as the One who owns all.Keywords: Abizai Abi, poems, Sinar Benar, Takmilah Theory